1985
DOI: 10.1088/0022-3727/18/5/018
|View full text |Cite
|
Sign up to set email alerts
|

Thermal recovery and thermoluminescence of room-temperature X-irradiated NaCl:Pb2+single crystals

Abstract: The thermoluminescence (TL) spectrum of NaCl:Pb2+ single crystals X-irradiated at room temperature consists of seven glow peaks that obey second-order kinetics. The bands in the wavelength spectrum of the emitted light correspond to different emissions of Pb2+ ions. A parallel study of the thermal stability of defects produced by the irradiation shows that the Pb+ ions and F-centres annihilate during TL; at the same time Pb2+ ions are recovered. A model is proposed in which holes and interstitials are trapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Besides the brightness, one important factor in selecting phosphor in color co-ordinates as was reported [21,35]. Ce 3+ known to be a sensitizer for Tb 3+ in many hosts [9][10][11][12][13][14]31]. The emission efficiency is the preferential factor for designing a new phosphor is then,we concluded that co-doping the Ce 3+ ions is a helpful way to modify the emission band of the KBr:Tb phosphor and thereby brightness can be enhanced successfully.…”
Section: Photoluminescencesupporting
confidence: 50%
See 1 more Smart Citation
“…Besides the brightness, one important factor in selecting phosphor in color co-ordinates as was reported [21,35]. Ce 3+ known to be a sensitizer for Tb 3+ in many hosts [9][10][11][12][13][14]31]. The emission efficiency is the preferential factor for designing a new phosphor is then,we concluded that co-doping the Ce 3+ ions is a helpful way to modify the emission band of the KBr:Tb phosphor and thereby brightness can be enhanced successfully.…”
Section: Photoluminescencesupporting
confidence: 50%
“…Such results have been reported on Rubidium halides doped with Tb 3+ by Manimozhi et.al. [4,23,[27][28][29][30][31][32][33][34]. Considering the fact that the new absorption appears on F bleaching, it appears more appropriate to assign the new absorption to an electron excess center.…”
Section: Optical Absorptionmentioning
confidence: 99%
“…TL studies on alkali halides have led to a good understanding of different aspects of the process, mechanism and mobile carriers [13,14] utilization of thermoluminescent phosphors for various applications like dosimetry [15], geology/geochronology [16], forensic sciences [17], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal treatments strongly modify the aggregation state of impurity in the host lattice [10]. Thus, it is reasonable to assume that the variations in the aggregation state of impurity produces differences in the relative positions and intensities of glow peaks.…”
Section: Discussionmentioning
confidence: 99%